2009
DOI: 10.1016/j.ijgo.2009.08.030
|View full text |Cite
|
Sign up to set email alerts
|

A report on the reproductive health of women after the massive 2008 Wenchuan earthquake

Abstract: The findings of this first population-based assessment of reproductive health following the massive Wenchuan earthquake may help in shaping public health measures benefiting women surviving large-sale disasters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
69
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(79 citation statements)
references
References 19 publications
6
69
0
4
Order By: Relevance
“…The PTSD prevalence of 8% reported by the women was higher than that reported by Priebe et al (2010) four years after the September 1997 earthquake in Italy (G1%) and lower than the 25% reported 4 years after the 1999 earthquake in Turkey and the 1999 earthquake in Greece (Kilic et al, 2006;Livanou et al, 2005;Priebe et al, 2010); however, there have been few studies that have documented the prevalence of PTSD in women solely after exposure to an earthquake with which to compare the results. The results of other studies on PTSD in relation to earthquakes concur with ours, especially with respect to the significance of the loss of social support (Cairo et al, 2010;Liu et al, 2010a). A study on PTSD with a small sample size (N = 44) in the same geographical area as that of our study has reported similar results (Ahmad et al, 2010).…”
Section: Discussionsupporting
confidence: 88%
“…The PTSD prevalence of 8% reported by the women was higher than that reported by Priebe et al (2010) four years after the September 1997 earthquake in Italy (G1%) and lower than the 25% reported 4 years after the 1999 earthquake in Turkey and the 1999 earthquake in Greece (Kilic et al, 2006;Livanou et al, 2005;Priebe et al, 2010); however, there have been few studies that have documented the prevalence of PTSD in women solely after exposure to an earthquake with which to compare the results. The results of other studies on PTSD in relation to earthquakes concur with ours, especially with respect to the significance of the loss of social support (Cairo et al, 2010;Liu et al, 2010a). A study on PTSD with a small sample size (N = 44) in the same geographical area as that of our study has reported similar results (Ahmad et al, 2010).…”
Section: Discussionsupporting
confidence: 88%
“…Rates of pelvic inflammatory disorders (PID), menstrual disorders, and reduced fertility were higher after the 2008 Wenchuan Earthquake [41]. In another report analyzing the obstetric outcome after the flood disaster in Kotlin Klodzki, Poland 1997, for 47 pregnant women who were injured in the flood pregnancy loss was 55.3% compared to no loss in a random control group of a 100 pregnant women in 1996.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the weeks after an 8.0-magnitude earthquake in China, women reported markedly increased symptoms of lower genital tract infection, pelvic inflammatory disease, and menstrual disorders [22]. After the 2001 attacks on the World Trade Center, women were more likely to report using psychiatric medications than were men [23].…”
Section: Introductionmentioning
confidence: 99%